Strengthening Disaster Resilient Schools through Earthquake Mitigation Socialization at SMAN 1 Kuripan, Lombok - Alfina Taurida Alaydrus; Muhammad Jarul Rozki; Ahmad Rifaldi Arahman; Nela Ranita Amanda; Zyiadatun Adawiah; Ayu Mona Erisa Marpaung; Siti Azizah; Syamsuddin; Suhayat Minardi; Rahmatun Inayah; Ika Umratul Asni Aminy; Adella Ulyandana Jayarti; Kormil Saputra (Asskruie: Jurnal Pengabdian Kepada Masyarakat, 2025)
Indonesia is a country with high tectonic activity and frequently experiences earthquakes that can result in significant damage and casualties. One of the earthquake-prone areas is West Lombok Regency, West Nusa Tenggara. To increase disaster awareness and preparedness, an earthquake mitigation outreach program was conducted at SMA Negeri 1 Kuripan. This activity used a participatory–educational approach through interactive presentations, discussions, and the delivery of material using the educational song “Kalau Ada Gempa” from BMKG. The results of the activity show an improvement in students’ understanding and enthusiasm regarding mitigation measures and the importance of preparedness within the school environment. This program is expected to serve as an initial step toward developing a disaster-resilient school in West Lombok.